Reflections on Judging - RICHARD A. POSNER (Harvard University Press, 2013)
My subject is the challenges that the federal courts face today, with particular emphasis on rising complexity. My approach is personal, in the sense of drawing heavily on my own experience as a judge. It is also realistic, in the sense of rejecting formalist approaches to law. Those are approaches premised on a belief that all legal issues can be resolved by logic, text, or precedent, without a judge â€™s personality, values, ideological leanings, background and culture, or real-world experience playing any role. The realist tradition in judging is the tradition shaped by such outstanding judges as John Marshall, Oliver Wendell Holmes, Louis Brandeis, Benjamin Cardozo, Robert Jackson, Learned Hand, Roger Traynor, and Henry Friendly. It is distinct from, though it overlaps, the â€œlegal realistâ€ movement of the 1920s and 1930s, which petered out, though not without leaving a mark.1 I need to say more about formalism and realism, which provide a contrast fundamental to this book, and will do so shortly.